PENYULUHAN TENTANG KANKER DAN PEMERIKSAAN IVA DI DESA CIJOLANG KECAMATAN LIMBANGAN KABUPATEN GARUT - Desy Syswianti; Nurul; Eti Suliyawati; Tanti Suryawantie; Zahara Farhan (LP4M STIKes Karsa Husada Garut, 2020)
Based on data on cervical cancer detection in 2016 for women aged 30-50 years, it was reported by 22 districts/cities in West Java (81.48%) with examinations of 62,220 people, from the target of screening women aged 30-50 years as many as 7,206,164 people so that the IVA coverage was 0.89%, and found a Positive VIA of 829 people (1.29%) of the total cervical examinations, City Districts that did not report Subang District, West Bandung District, City of Bandung, City of Cirebon, and City of Banjar. In Garut Regency, 1.21% were found positive for cervical cancer. (4) The high incidence of cervical cancer should be a concern for local governments in West Java Province, including the Garut Regency government. The government and the health community in Garut Regency must make every effort to prevent cervical cancer. The purpose of community service is expected to increase knowledge and positive attitudes of WUS in Cijolang Village, Limbangan District, Garut Regency in conducting early detection of cervical cancer with the IVA test method independently without waiting for a program from the government and assisting puskesmas in increasing the scope of the IVA Test examination in Cijolang Village, Limbangan District. Garut Regency. The method used is a lecture using video media about cervical cancer and the IVA Test. Followed by an IVA test. The media used are infocus, laptop, LCD.